Paediatric choroid plexus carcinoma: a retrospective case series from Karachi - Mustansir, Fatima; Baig, Erum; Angez, Meher; Khurram Minhas; Mushtaq, Naureen; Enam, Syed Ather (Journal of the Pakistan Medical Association, 2023)
The objective of this study is to report clinical, radiological, and histopathological characteristics of three paediatric patients diagnosed as Choroid plexus carcinoma seen at our hospital, between 2015 and 2020. Three patients were diagnosed with choroid plexus carcinomas between 2015 and 2018. The mean age at diagnosis was 1.3 years (range 8 months to 1.5 years). All the three patients had subtotal resection and received adjuvant chemotherapy. One patient also received adjuvant radiotherapy. Despite these treatment measures, residual disease was noted in all three patients and two patients were subsequently treated on palliative care grounds. The average duration of follow-up after the first surgery for all three patients was approximately 33 months. Attaining satisfactory outcome in patients with CPC is challenging. Our case series reflects the difficulty in achieving gross total resection and ensuring that the disease does not recur.